Truly New Orientation for Environmental Marketing - Kärnä, Jari (Ekonomika, 2002)
This paper is based on and modified from the following forthcoming research article: Kama, l., Hansen, E. & luslin, H. 2003. Social Responsibility in Environmental Marketing Planning, European Journal of Marketing, vol. 37.Forest related industries from four European countries were surveyed in order to examine social responsibility in business values and environmental emphasis in marketing. “Proactive green marketers” (companies emphasising sustainability but believing in free market system) emphasise environmental issues in marketing clearly more than traditional “consumption marketers”, and more than “reactive green marketers” (companies emphasising pursuing sustainability under governmental balancing). Thus, the example of these proactive companies should be the direction towards sustainable development in society.